Permeability and Release of Decontaminating Agent Used in Cytotoxic Reconstitution Units: Diffusion of Hydrogen Peroxide in IV Bags - Gérard, Camille; Huguet, Samuel; Escalup, Laurence; Ferry, Isabelle; Lafay, Marion; Fouque, Julien; Madar, Olivier; Rezai, Keyvan; Giard, Caroline (Pharmaceutical technology in hospital pharmacy, 2017)
Oxidant agents used for top-decontamination in cytotoxic reconstitution units may spread into IV bags. The amount of hydrogen peroxide passing through the bags and its release have been evaluated using wrapped or unwrapped infusion bags made of three layers of polyolefin (Freeflex®, Fresenius).